An optimized design to reduce eddy current sensitivity in velocity-selective arterial spin labeling using symmetric BIR-8 pulses. - Guo, J; Meakin, J; Jezzard, P; Wong, E (2015)
PURPOSE: Velocity-selective arterial spin labeling (VSASL) tags arterial blood on a velocity-selective (VS) basis and eliminates the tagging/imaging gap and associated transit delay sensitivity observed in other ASL tagging methods. However, the flow-weighting gradient pulses in VS tag preparation can generate eddy currents (ECs), which may erroneously tag the static tissue and create artificial perfusion signal, compromising the accuracy of perfusion quantification. METHODS: A novel VS preparation design is presented using an eight-segment B1 insensitive rotation with symmetric radio frequency and gradient layouts (sym-BIR-8), combined with delays after gradient pulses to optimally reduce ECs of a wide range of time constants while maintaining B0 and B1 insensitivity. Bloch simulation, phantom, and in vivo experiments were carried out to determine robustness of the new and existing pulse designs to ECs, B0 , and B1 inhomogeneity. RESULTS: VSASL with reduced EC sensitivity across a wide range of EC time constants was achieved with the proposed sym-BIR-8 design, and the accuracy of cerebral blood flow measurement was improved. CONCLUSION: The sym-BIR-8 design performed the most robustly among the existing VS tagging designs, and should benefit studies using VS preparation with improved accuracy and reliability.